The value of dual-energy CT virtual monoenergetic imaging and metal-artifacts reduction system after metal plate correction of congenital funnel chest in child: a single center retrospective study - Li, Chenglong; Xu, Chao; Lu, Liya; Dong, Lina; Du, Peng (Frontiers in Pediatrics, 2025)
ObjectiveThis study aimed to evaluate the utility of virtual monoenergetic (MONO) imaging and a Metal-Artifact Reduction System (MARs) algorithm for enhancing image quality in dual-energy computed tomography (DECT) of children with congenital funnel chest (CFC) following minimally invasive correction with stainless steel plate implantation.Materials and methodsWe retrospectively analyzed children with CFC who underwent thoracoscopic correction at our institution (January 2022 to August 2023). Their postoperative non-contrast chest CT scans were evaluated. Objective metrics (CT numbers, standard deviation-SD) were measured on five image series (120 kVp-like, 50 keV, 50 keV + MARs, 110 keV, 110 keV + MARs), and the absolute CT difference (|ΔCT|) and artifact index (AI) were calculated. Subjective image quality was scored by two independent radiologists. Given the non-normal distribution of data (Shapiro–Wilk test, P < 0.001), non-parametric tests (Friedman test with Wilcoxon post hoc analysis) were used for comparisons.ResultsA total of 114 children were enrolled. Objective metrics (SD, |ΔCT|, AI) on 110 keV images were significantly lower than on 120 kVp-like and 50 keV images (P < 0.001). The application of MARs further significantly improved image quality at both energy levels (P < 0.005). Subjective scores [presented as median (IQR)] confirmed that the 110 keV + MARs series provided the best image quality, which was significantly superior to all other groups (P < 0.001).ConclusionsThe high-energy VMI (110 keV) of the dual-energy CT can effectively reduce metal artifacts, and the combination of the 110 keV and MARs algorithm could further improve the image quality, which provides great assistance for the review and follow-up of children with CFC after metal plate correction.